A "Rash" Decision in Anesthetic Management: Benzyl Alcohol Allergy in the Perioperative Period. (24th June 2021) - Tripp, Michael; Ribeiro, Matthew; Kmiecik, Susanna; Go, Ramon
Abstract : Here, we present the case of a 54-year-old female presenting for outpatient ankle hardware removal who experienced severe total body pruritus along with a maculopapular rash persisting four days after the procedure. Patch testing demonstrated a sensitivity to benzyl alcohol, a preservative in propofol and several other anesthetics. The patient returned for left ankle arthroscopy a year later, and during that procedure, the anesthetic team avoided medications containing benzyl alcohol. This resulted in no pruritus or rash. Hypersensitivity reactions, ranging from contact dermatitis to anaphylaxis, are critical events in the perioperative period. Induction of general anesthesia has been implicated as the inciting event for perioperative hypersensitivity reactions. Benzyl alcohol is among a few excipients found in common anesthetic agents known to cause hypersensitivity reactions in susceptible patients. While reports of adult death are rare, infantile death due to benzyl alcohol has been described.